Jawabanmu

2014-05-01T19:18:20+07:00
1)  x + y = 6 ⇔ y = 6 - x
     x²+y² = 26 ⇔ x²+(6-x)² -26 = 0
                     ⇔ 2x² - 12x + 10 = 0
                     ⇔ x² - 6x + 5 = 0
                     ⇔ (x - 1)(x - 5) = 0
                          x = 1 atau x = 5
2)  2x² + 5y² = 12 untuk x = 4, maka
     2(4)² + 5y² = 12
     32 + 5y² = 12
             5y² = -20
               y² = -4 imajiner
              


kak yang no. 2 iq jawabannya harus - akar 5 dan - 2
2014-05-01T19:19:52+07:00
No 1
x + y = 6 >> x = 6-y substitusikan ke x^ + y ^ = 26
(6-y)^ + y^ = 26
36 - 12y + y^ +y^ = 26
2y^-12y+10=0
y^-6y+5=0
(y-5)(y-1)=0
y = 5 dan y=1

Jika y = 5, x= 6-5 =1
Jika y=1, x =6-1 = 5